A report of two pediatric tetanus cases - Aydın-Teke, Türkan; Bayhan, Gülstüm İclal; Afşarlar, Cağatay Evrim; Öz, Fatma Nur; Akansel, Abdul Ragip; Tanir, Gönül (The Turkish Journal of Pediatrics, 2011)
Tetanus is still a difficult-to-treat disease with high morbidity and mortality. Although it most commonly occurs in non-immunized children, it can also be seen in partially immunized or immunized children. We report herein two pediatric cases of generalized tetanus. Case 1 presented with signs of acute abdomen, while Case 2 presented with the typical clinical findings of tetanus. In this report, we highlight the importance of obtaining a history of the vaccination status of pediatric patients as an essential part of the evaluation. Furthermore, the differential diagnosis of non-immunized children with abdominal rigidity should include generalized tetanus.